BIOLOGI REPRODUKSI TUMBUHAN KANTONG SEMAR (Nepenthes ampullaria) - Fhina Marisya Putri; Fadiya Utami; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Nepenthes ampullaria is a unique species of pitcher plant due to its detritivorous nature and tendency to grow in clusters on the forest floor. This study aims to examine the reproductive biology of N. ampullaria, including flower morphology, flowering phenology, and pollination systems. The research was conducted using descriptive observational methods in its natural habitat. The results showed that N. ampullaria is dioecious, where male and female flowers are found on different individuals. The flowering process begins with the emergence of inflorescence buds that develop into flower clusters. Pollinator activity, dominated by nocturnal and diurnal insects, plays a crucial role in the success of fertilization. In addition to sexual reproduction through seeds, this species also demonstrates strong vegetative reproduction capabilities through basal shoots. Understanding this reproductive biology is essential as a basis for ex-situ conservation efforts and the cultivation development of this carnivorous plant.